Pesan Dakwah dalam Film Buya Hamka Vol 1 - Khalid, Muhammad Sandria (Lembaga Yasin AlSys, 2025)
Da'wah can be carried out by anyone using any medium as long as it is permitted by Islamic law. Nowadays, various media are used for da'wah, one of which is film. However, it is very rare to use film as a medium for delivering da'wah messages, as seen in the film Buya Hamka Vol 1. Therefore, this study aims to identify the da'wah messages in the film Buya Hamka Vol 1. This research employs content analysis with a descriptive qualitative approach, using the film Buya Hamka Vol 1 as the primary data source. The data collection technique used is coding sheets. The study concludes that the film Buya Hamka Vol 1 contains da'wah messages in the form of creed (aqidah), morality (akhlaq), and Islamic law (sharia). The da'wah messages related to creed amount to 7 messages or 35%, morality-related messages total 8 messages or 40%, and Islamic law-related messages account for 5 messages or 25%, out of a total of 20 da'wah messages.